Pengaruh Pemberian Ekstrak Black Garlic Terhadap Tekanan Darah Pada Penderita Hipertensi di UPTD Puskesmas Rowobungkul - Tut Wuri Prihatin; Eni Kusyati; Anisa Sofiana (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2021)
Introduction: Hypertension sufferers in Central Java experienced an increase of 12.9% from the results of the Basic Health Research in 2018. In Blora Regency, there were ± 36% of the population aged ≥18 years suffering from hypertension. Objectives: The research objective was to determine the effect of black garlic extract on blood pressure in hypertension sufferers at Rowobungkul Public Health Center. Methods: The research method was a quantitative study with a quasi-experimental approach two groups pre-posttest design. The samples of this research were 20 people with hypertension in Rowobungkul Health Center UPTD. The sampling technique used purposive sampling. The instrument used was a digital sphygmomanometer. Normality test data was calculated by using the Shapiro Wilk test with normally distributed data results, the difference with the paired sample t-test, and the 2-group difference test with the independent t-test. Results: The results showed that the average decrease in blood pressure after being given black extract is 33.20 mmHg and white garlic is 36.00 mmHg for systole, while black garlic extract diastole is 6.70 mmHg and white garlic extract is 7.40 mmHg. The results of the analysis of the effect of reducing blood pressure in patients with hypertension after giving black garlic and white garlic extracts with a p-value (systole) of 0.354 and a p-value of diastole (0.755). Conclusion: The conclusion is that there is no significant effect on black garlic extract compared to white garlic on blood pressure, meaning that the effectiveness of black garlic and white garlic extracts on blood pressure is the same.